INNOVATIVE METHODS OF TEACHING ENGLISH TO YOUNG CHILDREN. ("Conference on Universal Science Research 2023", 2023)
This article describes innovative methods of teaching English to young children. And it is said to enable the implementation of these methods in a new approach. In this article, you can get acquainted with meaningful and interesting methods of teaching English in preschool education and primary classes using modern information technologies and game methods.